Can Employers Access My AI Health Data? A Deep Dive into Privacy, Law, and Ethics - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The convergence of Artificial Intelligence AI and digital health has ushered in an era of unprecedented personal health insight, from smartwatches tracking s...
Keywords: Digital Health; Artificial Intelligence; Precision Medicine; Wearable Technology; Medical Ethics